(untitled) (Bangladesh Journal of Medical Education, 2022)
This cross sectional descriptive study was conducted to observe the quality of Pharmacology professional MCQ papers of different Universities of Bangladesh. For this purpose, total 80 MCQ papers of five universities dated from January 2007 to July 2015 were reviewed against a checklist to find out the coverage of recall, understanding and problem solving type questions, content coverage and construction of each question. The mean of recall, understanding and problem based type questions of all the universities were 92.1, 7.8 and 0.1 respectively and all of them statistically significantly differed from curriculum standard. All of the MCQ papers contained more than 75% recall type questions and 27.5% MCQ papers had only recall questions, Only 1(1.2%) MCQ papers contained 100 % topics (all the 11 groups). Eighteen (22.5%) contained 10 groups and 26.3% contained 9 groups out of 11. Forty percent MCQ papers contained less than 80% topics. Most of the stems of the MCQ were in the form of incomplete sentence (53.5%), 28.4% were in the form of complete statement and 16.8% were in the form of single word. Only 0.4% stem were in the form of clinical scenario. Fifty (62.5%) MCQ papers had defective stems and 68.75% had defective options. Total 14 (17.5%) MCQ papers were without any flaw but the rest 88.5% MCQ papers were with flaws either defective stem or faulty options or both. Findings of this study may be used to redefine the distribution of different type of questions in SAQ papers and to improve the quality of question papers by ensuring their coverage. Bangladesh Journal of Medical Education Vol.13(1) January 2022: 49-57